2008
DOI: 10.1542/peds.2007-1115d
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Immunizations and Other Clinical Preventive Services: A Needle and a Hook?

Abstract: Advances in technology have led to development of new vaccines for adolescents, but these vaccines will be added to a crowded schedule of recommended adolescent clinical preventive services. We reviewed adolescent clinical preventive health care guidelines and patterns of adolescent clinical preventive service delivery and assessed how new adolescent vaccines might affect health care visits and the delivery of other clinical preventive services. Our analysis suggests that new adolescent immunization recommenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 67 publications
1
37
0
1
Order By: Relevance
“…36 Sixth, the new adolescent vaccines are viewed to strengthen the so-called "adolescent vaccine platform," which means that the routinely recommended vaccines for adolescents may provide a prime opportunity to increase the delivery of other needed clinical preventive services or, in fact, may compete with them for time and other resources. 61 Certainly, there is also the possibility that adolescents will obtain vaccines in venues that cannot offer comprehensive services, but the aim for adolescents, as for children, is to maintain a medical home. 62 …”
Section: Unanswered Questionsmentioning
confidence: 99%
“…36 Sixth, the new adolescent vaccines are viewed to strengthen the so-called "adolescent vaccine platform," which means that the routinely recommended vaccines for adolescents may provide a prime opportunity to increase the delivery of other needed clinical preventive services or, in fact, may compete with them for time and other resources. 61 Certainly, there is also the possibility that adolescents will obtain vaccines in venues that cannot offer comprehensive services, but the aim for adolescents, as for children, is to maintain a medical home. 62 …”
Section: Unanswered Questionsmentioning
confidence: 99%
“…These recommendations are primarily based on studies of young children, published before the routine recommendations for adolescent immunization with Tdap, MCV4, and HPV vaccines; these studies noted improved childhood immunization rates due to practice-based reminder/recall. 6,7,10 Because adolescents present infrequently for primary health care visits, 5,12 reminder/recall for adolescent immunizations is attractive in concept. 13,14 Nevertheless, little evidence exists for the effectiveness of practice-based reminder/recall for adolescent immunizations, 15,16 although in one recent study in 4 practices researchers demonstrated increased immunization rates.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23] This work has laid the foundation for more recent research aimed at developing and evaluating interventions to increase adolescent vaccination. [24][25][26] These studies have centered primarily on HPV and influenza vaccines, given their lower coverage levels.…”
mentioning
confidence: 99%